2000
DOI: 10.1046/j.1365-2346.2000.00751.x
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy of the estimation of body weight and height in the intensive care unit

Abstract: A telephone survey of 20 English intensive care units (ICUs) confirmed that visual estimation of patient weight is often performed. Four experienced intensive care staff (three doctors and one nurse) estimated the weight and measured the height of 30 volunteers and the estimates were compared with accurate reference measurements. The estimates were shown to be significantly inaccurate for individual observers. We consider the degree of inaccuracy to be of clinical importance. However, pooling the individual es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 9 publications
3
33
0
1
Order By: Relevance
“…Panels of three observers, calculated as the mean or the median of three individual estimates, provided a more reliable estimation. This result is in accordance with another study conducted in healthy volunteers [1].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Panels of three observers, calculated as the mean or the median of three individual estimates, provided a more reliable estimation. This result is in accordance with another study conducted in healthy volunteers [1].…”
Section: Discussionsupporting
confidence: 93%
“…However, patients often cannot be weighed in hospital [1,2]. In a study conducted in an orthopaedic ward and a medical ward, Hilmer and colleagues found that only 24% (49/202) of all patients were actually weighed [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prerequisites for accurate measurement of body weight include weighing at the same time every day, weighing on the same calibrated scale, wearing clothing of approximately the same weight, and patients voiding or having an empty indwelling urinary catheter collection bag. 8,14,21 However, measurement of body weight in the critically ill is problematic because of episodes of hemodynamic instability, severity of illness, and the presence of comorbidities. To assist with monitoring body weight in the critically ill, the advent of weigh-beds, 8 the computerization of documentation, and the advances in technology have made weight measurements easier.…”
Section: Evaluating the Reliability Of Recorded Fluid Balance Eastwoodmentioning
confidence: 99%
“…Daily weight measurements provide a useful adjunct to the management of fluid balance in critically ill patients. 8 The relationship between recorded fluid balance and measured body weight is impacted by insensible fluid loss and inaccuracies associated with fluid balance documentation. Nonetheless, both methods are used in clinical practice to aid clinical decision-making and to optimize patient care.…”
mentioning
confidence: 99%